Clozapine-Induced Myocarditis and Pericarditis - Othman, Zahiruddin; Ahmad, Fazil; Halim, Ahmad Shahril Abdul; Ismail, Nurul Nadia (Japan International Cultural Exchange Foundation, 2014)
Objective: Clozapine is known to cause cardiac side-effects, including myocarditis, pericarditis and cardiomyopathy. A 50-year-old Malay man with schizoaffective disorder and tardive dyskinesia who developed transient tachycardia, low blood pressure and fever after 17 days of starting clozapine was studied. Result: Elevated creatinine kinase at 532 U/l along with WBC and neutrophil count at 21.40 and 16.83 x 1071 respectively indicated an acute myocarditis. Additionally, pericardium involvement was suggested by V1-V4 ST elevation and absence of T wave inversion. Conclusion: The emergence of tachycardia, low blood pressure and fever in patient who is recently started on clozapine treatment should be investigated for cardiac complications. Old age and concomitant treatment with sodium valproate possibly increased the risk of clozapine-induced cardiac side-effects